2019
DOI: 10.1002/adma.201904537
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Lithiophilic Mo2N‐Modified Carbon Nanofiber Architecture for Dendrite‐Free Lithium‐Metal Anodes in a Full Cell

Abstract: The pursuit for high-energy-density batteries has inspired the resurgence of metallic lithium (Li) as a promising anode, yet its practical viability is restricted by the uncontrollable Li dendrite growth and huge volume changes during repeated cycling. Herein, a new 3dimensional (3D) framework configured with Mo 2 N-mofidied carbon nanofiber (CNF) architecture is established as a Li host via a facile fabrication method. The lithiophilic Mo 2 N acts as a homogeneously pre-planted seed with ultralow Li nucleatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
123
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 43 publications
(69 reference statements)
4
123
0
Order By: Relevance
“…Luo et al. [ 20 ] demonstrated that a 3D framework configured with lithiophilic Mo 2 N‐mofidied carbon nanofiber as a Li host can not only effectively guide a uniform Li nucleation and deposition, but also suppress the Li‐dendrite formation. On the S cathode side, restricting shuttle effect, providing enough space for the Li 2 S deposition, and improving the conductivity of S cathode leads to high‐performance Li–S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al. [ 20 ] demonstrated that a 3D framework configured with lithiophilic Mo 2 N‐mofidied carbon nanofiber as a Li host can not only effectively guide a uniform Li nucleation and deposition, but also suppress the Li‐dendrite formation. On the S cathode side, restricting shuttle effect, providing enough space for the Li 2 S deposition, and improving the conductivity of S cathode leads to high‐performance Li–S batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleation overpotential could reflect the energy barrier of Li nucleation, indicating the lithiophilicity of the substrate . Therefore, to further evaluate the lithiophilic feature of the TiN‐VN@CNF, nucleation overpotentials of Li on different substrates were measured at a current density of 1 mA cm −2 (Figure k).…”
mentioning
confidence: 99%
“…Especially the electrode with Li excess only 100%, it displayed unstable cycling, low Coulombic efficiency and fast capacity decay. This may be ascribed to the controlled less Li excess, which inadequately compensate the Li loss by side reactions …”
mentioning
confidence: 99%
“…This is followed by the rapid Li + diffusion in vertical direction within the host, facilitated by the presence of abundant pores between interconnected nanocrystals and spaces between nanosheets (Figure1b). Such a Li + redistribution process, combined with the naturally strong lithiophilicity of metal nitrides [31] and high electron conductivity of NbN‐based host (674 S cm −1 ) that lower the Li nucleation energy, [36] could lead to the fast and uniform Li + ion flux, and eventually smooth Li deposition. During the following cycling, fresh Li may migrate into 2D arrays of NbN nanocrystals and compensate for the depletion due to the “self‐filling” effect of mesopores [18] .…”
Section: Figurementioning
confidence: 99%